Estimating the Prevalence of AATD Patients in the UK to Identify Underdiagnosis and Determine the Eligibility for Potential Augmentation Therapy - Newnham M; Quinn M; Turner AM (International Journal of COPD, 2023)
Michael Newnham,1,2 Mark Quinn,1 Alice M Turner1,2 1Institute of Applied Health Research, University of Birmingham, Birmingham, UK; 2University Hospitals Birmingham, Birmingham, UKCorrespondence: Alice M Turner, Institute of Applied Health Research, University of Birmingham, Birmingham, UK, Email a.m.turner@bham.ac.ukPurpose: Alpha 1 antitrypsin deficiency (AATD) is a genetic risk factor for chronic obstructive pulmonary disease (COPD). Whilst testing for the condition is relatively simple, there is a disconnect in published literature between genetic epidemiology and numbers of patients known to specialists. This makes planning services for patients difficult. We aimed to estimate the number of patients likely to have lung disease eligible for specific AATD therapy within the UK.Patients and Methods: The THIN database was used to determine the prevalence of AATD and symptomatic COPD. This, and published rates of AATD were used to extrapolate THIN data to the population size of the UK to give an indicative population size for symptomatic AATD patients who have lung disease. The Birmingham AATD registry was used to describe age at diagnosis, rate of lung disease and symptomatic lung disease for patients with PiZZ (or equivalent) AATD, together with the time from symptom onset to diagnosis, in order to aid interpretation of the THIN data and improve modeling.Results: THIN data showed COPD prevalence of 3%, and AATD prevalence of 0.005– 0.2%, depending on how stringently AATD diagnostic codes were applied. The majority of Birmingham AATD patients were diagnosed between the ages 46– 55, whilst patients recorded in THIN tended to be older. The rate of COPD was similar in the THIN and Birmingham patients diagnosed with AATD. Modelling to the size of the UK demonstrated a likely symptomatic AATD population of between 3016 and 9866 people.Conclusion: AATD is likely to be under-diagnosed in the UK. Based on projected patient numbers an expansion to specialist services is desirable, in particular if specific therapy for AATD such as augmentation were to be introduced to the healthcare system.Keywords: alpha 1 antitrypsin deficiency, chronic obstructive pulmonary disease, epidemiology